A THERMOPHILIC MICROBE PRODUCING DEXTRANASE FROM HEATED SUGAR CANE - Afaf Baktir; Zumrotul Koiriyah; Ali Rohman (Indonesian Journal of Chemistry, 2005)
A thermophilic aerobe microorganism designated NP4, was isolated from the heated sugar cane. It grew on dextran, and produced a thermoactive extracellular dextranase. Screening and isolation was done by assay of dextranase activity semi quantitatively on solid medium containing blue dextran. It provided several colonies with different morphology exhibited decolourized zones around, on culture plates containing blue dextran 2000R. The screening resulted in isolation of one microbe which efficiently assimilate dextran as carbon source. Dextranase production from the choised strain in liquid medium was conducted at room temperature for 8 hours with shaking speed of 125 rpm. The dextranase enzyme showed optimum pH of 8 and optimum temperature of 60 oC.